ROLE OF PHOSPHORUS, SILICON, AND CITRIC ACID IN ANATOMICAL TRAITS OF PEPPER PLANT CULTIVATED IN PLASTIC GREENHOUSE - Abdul Razzaq , A. H.; AL-Amery, N. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate effect of phosphorus, silicon, and citric acid on anatomical traits of pepper, This research was conducted at research stations, College of Agricultural Engineering Sciences, University of Baghdad, Jadiriyah Campus, during 2021-2022 season. The study employed factorial experiment within randomized complete block design (RCBD) with three replicates. The first factor included three levels of phosphorus (p) ( 0, 160, and 320 kg Ha-1 P2O5), the second factor included three levels of potassium silicate (s) ( 0, 75, and 100 kg Ha-1), while the third factor included four levels of citric acid (c ) ( 0, 2, 4, and 6 kg Ha-1). The results revealed that the P3S2C3 treatment had a significant increase in lateral root diameter (10.10 mm), P1S3C4 increased epidermis root thickness (30.93 µm), P3S3C2 led to increased root vascular bundle and stem,leaf cuticle thickness (284.9 µm, 6.63 µm, and 5.63 µm, respectively), the P1S2C4 treatment exhibited increased stem vascular bundle thickness (279.9 µm), The P1S2C2 showed increases in mesophyll thickness (106.03 µm), The P2S3C showed increases in leaf area (631.3 dcm2 plant-1) and P3S3C4 showed increases yield of plant (3.48 kg plant-1).